The Gacaca courts, post-genocide justice and reconciliation in Rwanda: justice without lawyers - Clark, Philip (Cambridge studies in law and society, 2010)
Machine generated contents note: Introduction; 1. Situating Gacaca: transitional justice themes; 2. Moulding tradition: the history, law and hybridity of Gacaca; 3. Interpreting Gacaca: the rationale for analysing a dynamic socio-legal institution; 4. The Gacaca journey: the rough road to justice and reconciliation; 5. Gacaca's modus operandi: engagement through popular participation; 6. Gacaca's pragmatic objectives; 7. Accuser, liberator or reconciler? - truth through Gacaca; 8. Law, order and restoration: peace and justice through Gacaca; 9. Mending hearts and minds: healing and forgiveness through Gacaca; 10. (Re)fusing social bonds: Gacaca and reconciliation; Conclusion